Correlates of tobacco product initiation among youth and young adults between waves 1–4 of the population assessment of tobacco and Health (PATH) study (2013–2018). (November 2022) - Cooper, Maria; Day, Hannah R.; Ren, Chunfeng; Oniyide, Olusola; Corey, Catherine G.; Ambrose, Bridget K.; Michael Cummings, K.; Sargent, James; Niaura, Ray; Pierce, John P.; Kaufman, Annette; Choi, Kelvin; et al.
Highlights: By follow-up, nearly 6 million youth used tobacco for the first time. By follow-up, nearly 2.5 million young adults used tobacco for the first time. Electronic nicotine devices had the highest proportion of new users. Cigarette and non-cigarette products share many correlates of initiation. Some noteworthy demographic differences exist in tobacco product initiation. Abstract: Introduction: While risk factors for cigarette smoking among youth and young adults are well-documented, less is known about the correlates of initiation of other tobacco products. This study aims to provide estimates and correlates of initiation among U.S. youth and young adults. Methods: Data on youth aged 12–17 (n = 10, 072) and young adults aged 18–24 (N = 5, 727) who provided information on cigarettes, electronic nicotine delivery systems (ENDS), cigars, pipe, hookah and smokeless tobacco use in Wave 1 (W1: 2013–2014)-Wave 4 (W4: 2016–2018) of the nationally-representative PATH Study were used to calculate ever use initiation and correlates of initiation by W4. Results: Nearly 6 million youth and 2.5 million young adults used tobacco for the first time between W1-W4. Approximately one quarter of youth and young adult ENDS never users initiated ENDS between W1-W4 of the PATH Study. Among youth, use of other tobacco products, ever substance use, and high externalizing problems were associated with initiation of most products. Among young adults, use of other tobacco products and ever substance use were associated with initiation of most products. In both youth and young adults, Hispanics were more likely to initiate hookah use than their non-Hispanic White counterparts. While male sex was a risk factor for most tobacco product initiation across both age groups, it was not associated with hookah initiation. Conclusions: Cigarette and non-cigarette products shared many correlates of initiation, although there are noteworthy demographic differences. Findings can help tailor product specific interventions to reach populations at risk during preliminary stages of use.